Influenza vaccine effectiveness in preventing hospitalizations with laboratory‐confirmed influenza in Greece during the 2014–2015 season: A test‐negative study. Issue 11 (26th April 2016) - Lytras, Theodore; Kossyvakis, Athanasios; Melidou, Angeliki; Andreopoulou, Anastasia; Exindari, Maria; Gioula, Georgia; Kalliaropoulos, Antonios; Tryfinopoulou, Kyriaki; Pogka, Vasiliki; Spala, Georgia; Malisiovas, Nikolaos; Mentis, Andreas
Abstract : The 2014–2015 influenza season was marked by circulation of antigenically drifted A/H3N2 strains, raising the possibility of low seasonal influenza Vaccine Effectiveness (VE). We assessed VE against hospitalization with laboratory‐confirmed influenza for the 2014–2015 season, using routine surveillance data. Non‐sentinel swab samples from Greek hospital inpatients were tested for influenza by RT‐PCR in three laboratories, covering the entire country. We estimated VE using a test‐negative design. Out of 883 patients with known vaccination status, 161 (18.2%) were vaccinated, and 392/883 patients (44.4%) tested positive for influenza, of whom 162 (41.3%) had type B and 151 (38.5%) had A/H3N2. Adjusted VE was 31.6% (95%CI: 2.9–51.8%) against any influenza, 46.8%, 95%CI: 12.5–67.6%) against type B and −1.9%, 95%CI: −69.5 to 38.7%) against A/H3N2. VE against non‐ICU hospitalization appeared to be higher, but the difference did not reach statistical significance. Circulating A/H3N2 viruses showed substantial antigenic drift, while about half of the type B strains were similar to the vaccine strain. Despite the antigenic drift of the A/H3N2 strains, the vaccine still offered substantial protection against hospitalization with laboratory‐confirmed influenza, mostly due to a surge in type B influenza late in the season. Vaccine coverage was low, even among groups targeted for vaccination, and considerable effort should be made to improve it. J. Med. Virol. 88:1896–1904, 2016 . © 2016 Wiley Periodicals, Inc.